2003
DOI: 10.1002/jcp.10298
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic acid inhibits PDGF‐induced mitogenesis and cyclin D1 expression via TGF‐β in mesangial cells

Abstract: Eicosapentaenoic acid (EPA), an omega-3 polyunsaturated fatty acid derived from fish oil, is efficacious in glomerular diseases where mesangial proliferation is a key event. We examined the mechanisms of action of EPA on platelet-derived growth factor (PDGF)-stimulated rat mesangial cell mitogenesis. EPA dose-dependently inhibited PDGF-stimulated [(3)H]-thymidine incorporation. PDGF-induced PDGF receptor autophosphorylation, an initial event for PDGF signaling, was not affected by 2 micro g/ml EPA. Similarly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…Previous studies have indicated that long-chain polyunsaturated fatty acids may modulate cell growth by releasing TGF-b (21). We asked whether 20-HETE inhibited cell proliferation by releasing TGF-b.…”
Section: Anti-tgf-b Antibody Reversed 20-hete-induced Inhibition Of Dmentioning
confidence: 97%
See 4 more Smart Citations
“…Previous studies have indicated that long-chain polyunsaturated fatty acids may modulate cell growth by releasing TGF-b (21). We asked whether 20-HETE inhibited cell proliferation by releasing TGF-b.…”
Section: Anti-tgf-b Antibody Reversed 20-hete-induced Inhibition Of Dmentioning
confidence: 97%
“…Recent studies indicate that the secretion, activity, and clearance of transforming growth factor-b (TGF-b) can be regulated by long-chain polyunsaturated fatty acids such as eicosapentaenoic acid (EPA) (21,22). EPA inhibits plateletderived growth factor (PDGF)-induced DNA synthesis by stimulating the secretion of TGF-b in mesangial cells (21).…”
Section: /Kmentioning
confidence: 99%
See 3 more Smart Citations